High-Density Microarray-Mediated Gene Expression Profiling of Escherichia coli - Wei, Yan (American Society for Microbiology, 2001)
A nearly complete collection of 4,290 Escherichia coli open reading frames was amplified and arrayed in high density on glass slides. To exploit this reagent, conditions for RNA isolation from E. coli cells, cDNA production with attendant fluorescent dye incorporation, DNA-DNA hybridization, and hybrid quantitation have been established. A brief isopropyl-β-d-thiogalactopyranoside (IPTG) treatment elevated lacZ, lacY, and lacA transcript content about 30-fold; in contrast, most other transcript titers remained unchanged. Distinct RNA expression patterns between E. coli cultures in the exponential and transitional phases of growth were catalogued, as were differences associated with culturing in minimal and rich media. The relative abundance of each transcript was estimated by using hybridization of a genomic DNA-derived, fluorescently labeled probe as a correction factor. This inventory provided a quantitative view of the steady-state level of each mRNA species. Genes the expression of which was detected by this method were enumerated, and results were compared with the current understanding of E. coli physiology.